Coffee protein profiles during fermentation using different yeast inoculation methods - Bressani, Ana Paula Pereira; Martinez, Silvia Juliana; Vilela, Leonardo de Figueiredo; Dias, Disney Ribeiro; Schwan, Rosane Freitas (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the protein profiles of natural and semidry fermented Coffea arabica, either subjected to treatments with different yeast inoculation methods with starter culture or to an uninoculated control. Saccharomyces cerevisiae CCMA 0543 and Candida parapsilosis CCMA 0544 were separately inoculated into coffee by directly spraying the cherries on a terrace or in buckets, for 16 hours before sun drying. Protein quantification showed a significant difference between the protein profiles of the samples collected after natural dry fermentation. The MALDI-TOF MS analysis generated a list of 96 peaks with different mass-to-charge ratios (m/z) in the samples collected at the beginning and the end of fermentation. The highest number of peaks in the natural dry coffee was observed at the end of fermentation in the samples inoculated with S. cerevisiae CCMA 0543, in bucket, and in C. parapsilosis CCMA 0544 sprayed on the terrace. However, in the semidry processed coffee, the highest number of peaks was observed in the initial fermentation, with a decrease in the peptide peaks after fermentation. The fermentation with different microorganisms, processing types, and inoculation methods affects m/z profiles, influencing the types of proteins found in coffee.